The digital ecosystem: The new politics of party organization in parliamentary democracies. (September 2021) - Dommett, Katharine; Kefford, Glenn; Power, Sam
Since at least the 1980s, scholars have highlighted parties' reliance on external actors, with Panebianco's 'electoral–professional' party model spotlighting the increasing role of professionals in supporting party activities and campaigns. Over successive decades, our understanding of the role of external actors, and particularly consultants, has grown. As parties have begun to embrace digital tools and technologies, however, it has become apparent that our understanding of party organization does not reflect the array of actors who support party activities. In this article, we draw on extensive interview data from Australia and the United Kingdom to offer a new conceptual framework – that we call the 'party-centred digital ecosystem' – to highlight the functions that different types of external actor provide for parties. Introducing the classification of CLANS to describe these different actors, we discuss the significance of this trend, highlighting the potential for increasingly porous organizational boundaries as parties call on different types of external actor for support.